2020
DOI: 10.3390/microorganisms8030374
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Wood Mice (Apodemus sylvaticus) Carrying Non-Tuberculous Mycobacteria Able to Infect Cattle and Interfere with the Diagnosis of Bovine Tuberculosis

Abstract: Mycobacterial infections caused by the Mycobacterium tuberculosis complex (MTC) and non-tuberculous mycobacteria (NTM) are of great medical and veterinary relevance. The aim of this research was to study whether small mammals play a role in the epidemiology of mycobacterioses. Four samplings of 100 traps were performed in each of three cattle farms with previous history of tuberculosis or NTM between 2017 and 2018. A total of 108 animals belonging to seven species were trapped, classified, and necropsied, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Hence the relevance of isolating opportunistic pathogens such as M. nebraskense and M. lentiflavum from wildlife is unclear. Only recently, a study in Spain tried to identify small mammals, mainly Apodemus sp., as the source of NTM infection in cattle which can lead to cross-reactive responses that can interfere with the diagnosis of tuberculosis ( 56 ). The authors identified six different NTMs ( M. intracellulare, M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the relevance of isolating opportunistic pathogens such as M. nebraskense and M. lentiflavum from wildlife is unclear. Only recently, a study in Spain tried to identify small mammals, mainly Apodemus sp., as the source of NTM infection in cattle which can lead to cross-reactive responses that can interfere with the diagnosis of tuberculosis ( 56 ). The authors identified six different NTMs ( M. intracellulare, M. avium subsp.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether these mycobacteria are able to colonize the mice or only pass through the animals. However, the movement of these animals leads to further spread ( 56 ) and may be problematic for livestock animals. The virulence of NTMs, including M. lentiflavum , in mice has been compared to the virulence of M. intracellulare and reported as lower ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…MTC infection among wild mammals from this region has been detected in wild boar (1.12%) and red deer (2.40%) [ 22 ]. Several species of NTM able to infect cattle and interfere with the diagnosis of bovine tuberculosis have been also detected in wood mice [ 18 ] and other wild species from the study area (Varela-Castro, unpublished data: wild boar, red deer, roe deer, badgers, foxes and stone martens).…”
Section: Methodsmentioning
confidence: 99%
“…Almost half of the MTC-positive cattle of the last ten years in the Basque Country were detected in farms A and C and NTM were also detected in these farms, while in farm B only M. avium subsp. avium was detected [ 18 ]. Farms A and B are dairy farms and farm C is a fighting bull farm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation